Phytochemical functional foods - Johnson, Ian (Woodhead Publishing, 2011)
Plant foods are rich in micronutrients, but they also contain an immense variety of biologically-active, non-nutritive compounds that contribute to colour, flavour and other characteristics. These phytochemicals have been increasingly linked to reducing the risk of chronic diseases such as cancer, osteoporosis and coronary heart disease. Edited by two leading experts in the field, and with a distinguished international team of contributors, Phytochemical functional foods assesses the evidence for their health benefits and reviews the key issues involved in successful product development. Part I reviews research on the health benefits of phytochemicals, including chapters on cardiovascular disease, cancer, bone and gastrointestinal health, as well as the functional benefits of particular groups of phytochemicals such as phytoestrogens, carotenoids and flavonoids. Part II considers the key safety and quality issues in developing phytochemical products. There are chapters on establishing appropriate intake levels, testing the safety of phytochemicals and establishing health claims through clinical trials. Part II also covers such issues as extracting and enhancing phytochemical compounds for use in food products. Phytochemical functional foods will establish itself as a standard reference on one of the most important sectors in the functional foods market. Book jacket.